2006
DOI: 10.3354/dao072001
|View full text |Cite
|
Sign up to set email alerts
|

Association between environmental stress and  epidermal papillomatosis of roach Rutilus rutilus

Abstract: We studied the association between environmental stress and epidermal papillomatosis of roach Rutilus rutilus L. in Finnish waters using a 'matched pairs' design. Populations impacted by industrial and/or sewage effluents were compared to reference populations from pristine sites. We examined both the prevalence (proportion of diseased fish) and intensity (number of scales covered by tumors) of the disease. Results of Generalized Linear Mixed Models (GLMM) indicated that the risk of papillomatosis was 7.5 time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…The present result is in concordance with several field studies which have shown that the prevalence of papillomatosis in fish populations is increased by contaminants (Baumann, et al 1996;Hayes, et al 1990;Kortet, et al 2002;Mikaelian, et al 2000;Premdas, et al 1995;Smith, et al 1989;Vethaak, et al 1992). Most recently the connection was found between higher papillomatosis prevalence in roach populations and lake sites which were impacted by industrial and / or sewage effluents (Korkea-aho, et al 2006a). Beside the connection with effluents and fish papillomatosis found in the field studies, only Grizzle et al (1984) has studied before this connection experimentally.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present result is in concordance with several field studies which have shown that the prevalence of papillomatosis in fish populations is increased by contaminants (Baumann, et al 1996;Hayes, et al 1990;Kortet, et al 2002;Mikaelian, et al 2000;Premdas, et al 1995;Smith, et al 1989;Vethaak, et al 1992). Most recently the connection was found between higher papillomatosis prevalence in roach populations and lake sites which were impacted by industrial and / or sewage effluents (Korkea-aho, et al 2006a). Beside the connection with effluents and fish papillomatosis found in the field studies, only Grizzle et al (1984) has studied before this connection experimentally.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, papillomatosis of fish has been proposed as an indicator of contaminated waters (e.g. Baumann, et al 1996;Korkea-aho, et al 2006a). Papilloma prevalence increased in caged black bullheads (Ictalurus melas) in final oxidation pond of domestic chlorinated wastewater (Grizzle, et al 1984).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Nunez et al (1989) discussed the higher rates of certain neoplasms in female fish due to the promoter oestradiol, Kimura et al (1984) found the prevalence of chromatophoromas in croakers Nibea mitsukurii in coastal waters in Japan to be higher in males than in females. Poulet et al (1994) found no difference between the prevalences of papillomas and carcinomas in male and female brown bullheads, but papillomatosis in roach Rutilus rutilus was 7.5 times higher in male than in females (Kortet et al 2002), a finding supported by Vainikka et al (2004) and Korkea-aho et al (2006). Among squamous cell carcinomas, Herman (1988) described enzootic squamous cell carcinomas in mature male rainbow smelt Osmerus mordax in a pond in Maine, US, and Morrison & Macdonald (1995) also reported a squamous cell carcinoma in the jaw of a male rainbow smelt O. mordax, and speculated about male hormonal influence.…”
Section: Discussionsupporting
confidence: 67%
“…Levels of pollutants in sentinel organisms and the responses that these pollutants trigger in individuals have been successfully used as biomarkers of pollution (Broeg et al, 1999;Handy et al, 2002;Williams and Mackenzie, 2003;Au, 2004). Histopathology has been shown to be a useful tool for detecting sublethal and chronic damage of pollution in marine organisms (Stehr et al, 1998;Bernet et al, 1999;Korkea-aho et al, 2006). Since fish parasites can reflect adverse effects of complex and variable environmental stresses (Lafferty, 1997;Landsberg et al, 1998;Lafferty and Kuris, 1999;MacKenzie, 1999;Dzikowski et al, 2003;Williams and Mackenzie, 2003), the study of fish parasite community structure has been proposed as a more sensitive indicator than the study of fishes themselves (Landsberg et al, 1998).…”
Section: Introductionmentioning
confidence: 99%